Motif Saik Galamai Dalam Bentuk Typeface SAGA (International Forum of Researchers and Lecturers, 2023)
Saik Galamai is a decorative variety originating from West Sumatra, the Saik Galamai motif itself comes from Minangkabau kgas food, namely galamai. Which is cut in the shape of a kite so that this form of the Saik Galamai motif is created. Making Galamai must be done carefully and with great care. It requires high precision and caution. The design of the typeface inspired by the Saik Galamai Minangkabau decoration is a form of cultural preservation. In addition, the application of the saik galamai motif into typeface exploration is a new innovation made to reintroduce local culture to the target audience in the form of typefaces. The method used in this design is the 4D method through 5W+1H data analysis. The results of this design will produce a new typeface which includes uppercase, lowercase, numerals, and punctuation characters which are presented in visual form through media, posters, stickers, X-banners, keychains and tote bags.